KEPEMIMPINAN KEPALA SEKOLAH BERBASIS MICRO-HABITS COACHING DALAM MENINGKATKAN KINERJA PEDAGOGIK GURU DI SMP BP AL MUTHOHHAR - Arlin Nurmaliani; Yodi Ahmad Sirojudin; Tri Purwati; Nissa, Chairunissa; Reczy Setian Suharno; Rohendi Ali; Faiz Karim Fatkhullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The principal's leadership has a strategic role in improving the quality of education, particularly through strengthening the pedagogical performance of teachers as the spearhead of the learning process in schools. As time progresses, the teaching and learning process is required to become more innovative to foster teacher professionalism. However, this remains difficult to achieve, partly due to a lack of adaptation to current developments. To encourage this adaptation, a study was conducted on Principal Leadership based on Micro-Habits Coaching to Improve Teacher Pedagogical Performance. The research method used was a descriptive qualitative approach, encompassing observation, interviews, and documentation. The results also revealed that small, consistent changes in habits significantly impacted the quality of lesson planning, teaching strategy variations, classroom management, and teachers' ability to conduct formative assessments.